Moderation effect of firm size and audit complexity on the influence of internal auditor on audit delay / Rediyanto Putra, Sumadi Sumadi and Berlina Yudha Pratiwi - Putra, Rediyanto; Sumadi, Sumadi; Pratiwi, Berlina Yudha (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2018)
This study aimed to prove the influence of internal auditors on audit delay and also to prove the moderate effect of audit complexity and firm size on the influence of internal auditors on audit delay. This research was conducted on all public companies listed in the Indonesia Stock Exchange during 2013 until 2015. The study found that the audit delay of public companies ranges from 6 days to 179 days. The results showed that internal auditors, audit complexity, and firm size proved to have an effect on audit delay. The results also show that only firm size has a moderating effect on the influence of internal auditors on audit delay.